1996
DOI: 10.3758/bf03204792
|View full text |Cite
|
Sign up to set email alerts
|

Introductory psychology laboratories using graphic simulations of virtual subjects

Abstract: Graphical simulations of the behavior of virtual subjects in laboratory or field microworlds were developed to teach research principles to introductory psychology students. Students conduct studies in laboratory classes, assuming the primary role of being an experimenter. Microworld modules were designed to foster the flexible exploration of important steps in the research process, including hypothesis generation, research planning and design, behavioral observation or testing, and data summarization and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…CYBERSHOPPER subjects often remarked about particular stores, and most insisted on taking their shopping lists home with them (Rajala, 1996). Other MW studies have typically reported similar indications of interest (Colle & Green, 1996;Ekker et aI., 1988;Elsmore, 1994;Lowman & Norkus, 1987).…”
Section: Experimental Realismmentioning
confidence: 54%
See 1 more Smart Citation
“…CYBERSHOPPER subjects often remarked about particular stores, and most insisted on taking their shopping lists home with them (Rajala, 1996). Other MW studies have typically reported similar indications of interest (Colle & Green, 1996;Ekker et aI., 1988;Elsmore, 1994;Lowman & Norkus, 1987).…”
Section: Experimental Realismmentioning
confidence: 54%
“…More generally, the term has been associated with computer-simulated environments often used for educational or training purposes (Albers, Brand, & Cellerier, 1991;Good, 1987;Keys, Fulmer, & Stumpf, 1996). In psychological literature (e.g., Colle & Green, 1996;Funke, 1991;Perkey, 1986), and especially in the field of decision making, the term has been more rigorously defined. Berndt Brehmer (1992) and Dietrich Dorner (Brehmer & Dorner, 1993) have most clearly delineated the concept to mean computergenerated simulation environments that real subjects interact with and that possess, to varying degrees, a dynamic (see below), complex (i.e., necessitating multiple considerations by the subject), and opaque (i.e., necessitating exploration) character.…”
mentioning
confidence: 99%
“…Many educational virtual labs (e.g., Colle & Green, 1996;Hachette, Zivian, Zivian, & Okada, 1999;Keenan & Keller, 1980) are built around set research examples. The Utah Virtual Lab differs from these educationally valuable virtual labs in that it allows instructors to create custom research examples.…”
Section: Discussionmentioning
confidence: 99%
“…Early innovation (Bradley, 1978;Lehman, Starr, & Young, 1975;Rywick, 1975) and steady evolution (Bradley, 1993) have combined to lay a conceptual and practical groundwork for teachers to use computer simulations of laboratory experience as educational tools for teaching the principles of research methods. Among recent examples is the virtual lab developed by Colle and Green (1996), with graphical simulations of virtual subjects. Brown's (1999) Wildcat World allows students to design studies for doing research on human facial features.…”
mentioning
confidence: 99%
“…That is, could we increase appreciation for psychology as a science through “virtual engagement,” by having students observe a laboratory demonstration in which other students acted as participants and experimenters, rather than conducting the research themselves? Past research notes that engagement through computer simulation can increase interest and motivation in introductory psychology students (e.g., Colle & Green, 1996). Yet, little research has examined whether observing others conducting experiments can increase appreciation for psychology as a science.…”
mentioning
confidence: 99%